Clinical Characteristics and Prognostic Factors Affecting Clinical Outcomes in Cytomegalovirus Retinitis Following Allogeneic Hematopoietic Stem Cell Transplantation - Qiaozhu Zeng; Yuou Yao; Jing Hou; Heng Miao (Biomedicines)
Background/Objectives: This study aimed to evaluate the clinical characteristics and identify the prognostic factors affecting visual outcomes, retinal detachment, and recurrence in cytomegalovirus retinitis (CMVR) patients following allogeneic hematopoietic stem cell transplantation (allo-HSCT). Methods: A retrospective analysis of 54 CMVR patients (84 eyes) who underwent allo-HSCT between 2015 and 2024 was conducted. Ophthalmologic and systemic evaluations were performed. The visual outcomes were classified as improvement, stabilization, and deterioration. Logistic regression and LASSO regression models were used to identify the prognostic factors. Results: Improved or stabilized visual outcomes were found in 22 eyes, while 62 eyes suffered from deterioration. Larger lesion areas were independently associated with poorer visual outcomes (OR 0.989, p = 0.002). Eight (9.5%) eyes had rhegmatogenous retinal detachment and thirteen (15.5%) eyes suffered from recurrence. Retinal detachment was significantly predicted by higher baseline aqueous CMV DNA load (OR 5.087, p = 0.026). Macula involvement (OR 5.322, p = 0.032) and more intravitreal injections (IVs) (OR 1.263, p = 0.008) were independent risk factors for recurrence. No systemic factors were found to be associated with the clinical outcome of eyes with CMVR. Conclusions: Ocular characteristics, rather than systemic factors, were more useful to predict the clinical outcome of eyes with CMVR. Routine ophthalmic screening and early intervention are essential to improving outcomes in this vulnerable population.